Globalisation: Exodus of German industry? - Rolf Jungnickel (Intereconomics, 1996)
Many commentaries on the present economic situation contend that Germany is increasingly “exporting jobs” rather than producing competitive goods and services. Can Germany continue to compete effectively with other business locations in the battle for mobile investment capital?
Keywords: 330; Germany